Larger WIC Cash Value Benefit for Vegetables and Fruit Is Associated With Lower Food Insecurity and Improved Participant Satisfaction in WIC Families With Children. (14th June 2022) - Tsai, Marisa; Au, Lauren; Ritchie, Lorrene; Anderson, Christopher; Martinez, Catherine; Whaley, Shannon
Abstract: Objectives: In response to the COVID-19 pandemic, the USDA announced a temporary augmentation of the cash value benefit (CVB) for vegetables and fruits across all Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) agencies nationally, increasing the child CVB from 9 to 35/month for 4 months in the summer of 2021. The augmentation has continued since October 2021, with children ages 1 to 4 years receiving a CVB of 24/month. This study aimed to understand if augmenting the value of the WIC CVB for vegetables and fruits is associated with access to fruits and vegetables, fruit and vegetable intake (FVI), household food insecurity, and WIC program satisfaction among WIC participants from Los Angeles County, California. Methods: This longitudinal, observational study of the 2021 CVB augmentation involved data collection using surveys at three time points: baseline (May 2021), midpoint (September 2021, before the CVB reduced from 35 to 24/month) and endpoint (May 2022, to be conducted). Detailed data on child FVI (using the NHANES Dietary Screener Questionnaire), household food security (using the USDA 6-item food security screener), and parental perception of the CVB changes were collected. Descriptive statistics and changes in study outcomes for respondents from baseline to midpoint were calculated in the full sample and stratified by race and ethnicity. Results: 1, 673 families completed both baseline and midpoint surveys. Following the increased CVB amount (9 to 35), the proportion of families reporting the benefit was 'not enough' decreased (89% to 23%) and the proportion saying the benefit was 'just right' increased (7% to 73%) (p < 0.0001). Household food insecurity decreased following the increase in CVB (55% to 44%, p < 0.0001). Child FVI decreased between baseline and midpoint surveys (2.43 vs 2.37 cups/day, p < 0.01). Baseline to midpoint change in FVI did not differ significantly by race and ethnicity (p = 0.19). Conclusions: A short-term increase in WIC CVB was associated with improved participant experience and higher food security in California WIC participants. Longer-term increases in CVB may be needed to improve child fruit and vegetable intake. Funding Sources: Robert Wood Johnson Foundation Healthy Eating Research Program and The David and Lucile Packard Foundation.